IMPLEMENTASI METODE KOOPERATIF TAI (TEAM ASSISTED INDIVIDUALIZATION) DALAM UPAYA MENINGKATKAN PEMAHAMAN SISWA MATERI BILANGAN BULAT DI KELAS IV SD IT ISLAMIYAH BELINTENG TAHUN AJARAN 2025/2026 - Situmorang, Nisa Anggraini; Ramadianti, Astria Ayu; Herdyana, Thessa (Program Studi Pendidikan Guru Sekolah Dasar Universitas Nahdlatul Ulama Sumatera Utara, 2025)
The importance of using varied learning methods in an educational context is increasingly evolving with the times. One aspect that requires special attention is mathematics learning for elementary school students. This study aims to: (1) determine whether the implementation of the cooperative TAI method can improve students' understanding of positive and negative integer arithmetic operations in fourth-grade students at SD IT Islamiyah Belinteng, (2) determine whether there are differences in student activity levels before and after the implementation of the cooperative TAI method in learning in fourth-grade students at SD IT Islamiyah Belinteng. This type of research is classroom action research. The subjects were 24 fourth-grade students at SD IT Islamiyah Belinteng, consisting of 15 boys and 9 girls. The researchers used the action research model by Kemmis and McTaggart. This research was conducted in two action cycles. The first cycle consisted of six meetings and the second cycle also had six meetings. Each cycle included planning, implementation, observation, and reflection. The results of the first cycle of research showed that the percentage of students whose scores were above the KKM only reached 62.5%, so they still could not achieve the research success criteria. In the second cycle, the steps of the TAI (Team Assisted Individualization) cooperative method to improve student success were carried out. The percentage of students' scores above the KKM in the second cycle increased to 87.5%. And also the level of student activity increased from 54.14% during the pre-cycle, 74% in the first cycle and the second cycle got a score of 88.83% and was included in the good category. Based on the results of the study, it can be seen that the TAI (Team Assisted Individualization) cooperative method is able to improve student understanding and learning outcomes.